Surface morphology study in laser paint removal mechanisms on selected national car coated substrate - Mohammad Khairul Azhar Abdul Razab; Mohammad Suhaimi Jaafar; Nor Hakimin Abdullah; Mohamad Faiz Mohd Amin; Mazlan Mohamed (Asian Research Publishing Network (ARPN), 2016)
Thirty six rectangular shapes of two type’s national car coated substrate samples were irradiated by using Nd: YAG laser for paint removal. The best and worst crater depth of highest laser paint removal efficiency was selected for surface morphology analysis by using Nova NanoSEM 450. The results show the surface texture of the crater depth was changed and varies based on the paint residue left after the paint stripping process.